Visualising Career Progression for ICT Professionals and the implications for ICT Curriculum Design in Higher Education - Von Konsky, Brian; Jones, A.; Miller, C. (Auckland Univeristy of Technology (AUT), 2013)
The current environment in higher education calls for more consideration of the linkages between ICT curriculum development, skills capabilities and industry, particularly in light of recent changes in quality and standards agencies. This paper evaluates ICT career progression visualisation methodology and has a threefold purpose: to contribute to a holistic approach to curriculum design and management; to add to materials that aid graduates to better prepare initial professional practice choices for employment in the ICT profession; and to facilitate further dialogue with industry representatives ,higher education providers and other ICT stakeholders to ensure undergraduate curricula authentically reflects the skills required within the ICT profession. This paper evaluates SFIA-based tools intended to enable educational designers to visualise ICT career progression pathways and thus inform curriculum design in higher education. Several visualisation techniques are compared using SFIA-based skillsets that were previously published in the literature. The evaluation demonstrates extended radar diagrams are an effective visual representation for capturing the level at which SFIA skill sets are practiced. The research indicates that such representations are well positioned to enhance dialogue amongst stakeholders and contribute to the design of ICT curriculum in a manner that better prepares students for ongoing development in the profession.